2019
DOI: 10.1021/acssuschemeng.8b05150
|View full text |Cite
|
Sign up to set email alerts
|

Developing a Novel Layered Boron Nitride–Carbon Nitride Composite with High Efficiency and Selectivity To Remove Protonated Dyes from Water

Abstract: A layered boron nitride (BN)−carbon nitride (CN) composite has been successfully synthesized by calcinating a mixture of BN nanoparticles and urea at 600 °C, wherein CN is formed from the thermal polymerization of urea during the calcination process. TEM analyses confirm that the BN-CN composite has a layered structure, being different from the morphologies of BN nanoparticles and CN. FTIR, XRD, and NMR results support that the layered BN-CN composite is most likely formed via the dehydration reaction between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 59 publications
2
22
0
Order By: Relevance
“…As shown in Figure 4(a), the adsorption rates of BB and CBB in Cd(II) contaminated water depend on the pH values and show similar trends. e adsorption rates of CBB increased from 66.78% to 90.66%, respectively, over the pH values range from 3 to 7, while the adsorption of Cd(II) tends to be stable when pH is greater than 7. erefore, the optimal pH of CBB on the Cd(II) removal efficiency is 7. is is consistent with the results reported for heavy metal removal from industrial wastewater using chitosan-modified oil palm shell charcoal which was in the pH values range of 6.8-7.1 [47]. erefore, our results demonstrated that pH is one of the most essential parameters in the Cd(II) adsorption process and might change the function groups, mainly oxygen-containing groups, of CBB [51].…”
Section: Effect Of Ph Contact Time and Dose On The Cd(ii)supporting
confidence: 93%
See 1 more Smart Citation
“…As shown in Figure 4(a), the adsorption rates of BB and CBB in Cd(II) contaminated water depend on the pH values and show similar trends. e adsorption rates of CBB increased from 66.78% to 90.66%, respectively, over the pH values range from 3 to 7, while the adsorption of Cd(II) tends to be stable when pH is greater than 7. erefore, the optimal pH of CBB on the Cd(II) removal efficiency is 7. is is consistent with the results reported for heavy metal removal from industrial wastewater using chitosan-modified oil palm shell charcoal which was in the pH values range of 6.8-7.1 [47]. erefore, our results demonstrated that pH is one of the most essential parameters in the Cd(II) adsorption process and might change the function groups, mainly oxygen-containing groups, of CBB [51].…”
Section: Effect Of Ph Contact Time and Dose On The Cd(ii)supporting
confidence: 93%
“…Adsorption. pH, an important parameter for affecting heavy metals adsorption, could affect the surface potential, counter ions concentration on the functional groups, and ionization degree of adsorbents [47][48][49][50]. To examine the effect of pH on the Cd(II) adsorption, the pH values were varied from 3 to 8.…”
Section: Effect Of Ph Contact Time and Dose On The Cd(ii)mentioning
confidence: 99%
“…Based on our previous work, boron nitride is synthesized by oxygen restriction method [26] . Typical diffraction peaks around 26.6 and 41.8° are shown in Figure 1(a).…”
Section: Resultsmentioning
confidence: 99%
“…The adsorption of four dyes, MG, AO, CV and RhB, on MMWCNTs were tested over a wide pH range from 4.0 to 10.0. However, the adsorption process of NR was investigated in a relative narrow pH range from 4.0 to 7.0 as precipitates would be formed under alkaline conditions (Guo et al 2019). As illustrated in Figure 2, the adsorption amounts for MG (Figure 2 electrostatic attraction with cationic dyes under increased pH values, thus the adsorption amounts of dyes gradually increased.…”
Section: Effect Of Ph and Common Ionsmentioning
confidence: 99%